2019
DOI: 10.3390/nu11102398
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella Review of Systematic Reviews on Food Choice and Nutrition Published between 2017 and-2019

Abstract: The objective of this umbrella review was to provide an update on the latest knowledge in the field of food choice and nutrition. Databases Scopus and ISI-Web of Science were searched for “food choice” AND nutrition. Papers were included if they were systematic reviews published between January 2017 and August 2019 on any subpopulation group. In total, 26 systematic reviews were kept. Data were extracted with a predetermined grid including first author, publication year, country, population group, explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 80 publications
1
26
0
1
Order By: Relevance
“…It may not be realistic to expect consistent and large intervention effects on all outcomes due to the short intervention duration. The findings of our study support the findings of other research, which concluded that nutrition education interventions should be implemented as part of a comprehensive approach [23,69]. Nutrition education with a strong focus on increasing procedural knowledge could be combined with more skills-related cooking interventions that take into account planning and managing, selecting, preparing, and eating healthy foods [25,70,71].…”
Section: Discussionsupporting
confidence: 86%
“…It may not be realistic to expect consistent and large intervention effects on all outcomes due to the short intervention duration. The findings of our study support the findings of other research, which concluded that nutrition education interventions should be implemented as part of a comprehensive approach [23,69]. Nutrition education with a strong focus on increasing procedural knowledge could be combined with more skills-related cooking interventions that take into account planning and managing, selecting, preparing, and eating healthy foods [25,70,71].…”
Section: Discussionsupporting
confidence: 86%
“…Healthy eating and food choices during adolescence are important for supporting growth and for preventing future health problems in adult life [ 48 ]. Young people following an unhealthy diet have higher odds of weight increase [ 49 , 50 , 51 ], with plethora of possible negative health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Macronutrient content is only one of many factors influencing adherence. Dietary choices and behaviors are complex and determined by different individual-level factors (e.g., food preference, knowledge), cultural factors (e.g., social support and social norms), economic factors (e.g., income), and the nutrition environment (e.g., access, availability) [ 56 ]. Ideas to increase adherence include supplying food, close monitoring, clear diet instructions, opportunities for participants to measure their own adherence (e.g., ketones, tallying carbs, CGMs), personalized advice and recommendations acknowledging participants efforts and goals, working with participants through life challenges experienced during the study protocols, and framing study adherence as a way of having some control of their lives.…”
Section: Discussionmentioning
confidence: 99%